Rubble & crew. Construction crew to the rescue! [videorecording (DVD)] - Zweig, Bradley (Paramount, 2024)
Grab your hard hats and get ready to bow wow build with Rubble & Crew! First, join the construction team as they build a beaver a new home. Then, the crew switches to cleanup mode when construction on Cafe Carl's new popcorn restaurant pops out of control, and PAW Patrol's Marshall stops by to inspect Builder Cove₂s first-ever fire station! Plus, Mix and Rubble are starstruck when they meet their favorite TV renovation star, Hank Hammer, and there's so much more with over 2 hours of construction adventures!